THE TEACHERS EFFORTS IN INCREASING THE FLUENCY OF MEMORIZING THE QURAN AT THE HOUSE OF TAHFIZ SUTAN IBNU HASYIM, MEDAN SELAYANG - Harmansyah Ramadhan; Lailatul Hasanah (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to find out where the problem of the lack of fluent memorization of some students at the Tahfidz House ofSutanIbnu Hasyim Medan. Tahfidz House of Sultan Ibnu Hasyim is one of the places to memorize the Qur'an in Medan City with a two-year specialization program. The researcher who is also a teacher at Tahfidz House ofSutanIbnu Hasyimassesses the need for this research. Because in memorizing the Quran is not just memorizing verses but how to maintain the memorization itself. This research uses qualitative and case studies with observation and interview data collection techniques. In addition, data are also presented using a descriptive approach in the form of words and writings to clarify the data collected and analyzed. After the research was carried out, it was found that the problem point was the lack of fluent memorization of some students, namely the lack of interest and awareness of students to do daily Repetition personally. To solve this problem, the researcher emphasizes the students to do personal repetition and motivates how important it is to rebuild memorization.Keywords:Fluency of Memorization, Al-Quran, Students